The Causes of the Occurrence and Spheres of Restoration of Chateau Brownfields: A Search for Causality on the Example of Properties in the Moravian-Silesian Region, Czech Republic - Kamila Turečková (Land, 2023)
Scientific research in the area of chateau brownfields is quite new and thus offers room for interesting findings and insights. This text presents the results of a pilot study in search of causality between the causes of the occurrence and spheres of restoration of chateau brownfields in the Moravian-Silesian region in the Czech Republic, where chateau settlements are considered an urban phenomenon of the cultural landscape. Out of a total of 88 chateaux, 40 have received brownfield status over the years, of which 28 are currently regenerated. The main reason why the chateaux were abandoned can be found in the inappropriate economic activities that took place in them, which originated mainly in the directive decision on their functionality at the end of the Second World War. Most of the chateau brownfield sites are still abandoned or currently for sale, and many others have been regenerated for tourism and public sector services. The causality analysed between the causes of their occurrence and their restored function reflects the logical and economic context characteristic of a time of restoration and the general desire of the public sector to reduce the number of brownfield sites in its cadastral area.